Initial Risk Matrix, Home Resources, Ability Development and Children's Achievement - Manfred Laucht; Katja Coneus; Dorothea Blomeyer; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper investigates the development of basic cognitive, motor and noncognitive abilities from infancy to adolescence. We analyse the predictive power of these abilities, initial risk conditions and home resources for children's achievement. Our data are taken from the Mannheim Study of Children at Risk (MARS), an epidemiological cohort study, which follows the long-term outcome of early risk factors. Results indicate that differences in abilities increase during childhood, while there is a remarkable stability in the distribution of the economic and socio-emotional home resources during childhood. Initial risk conditions trigger a cumulative effect. Cognitive, motor and noncognitive abilities acquired during preschool age contribute to the prediction of children's achievement at school age.
Keywords: D87; I12; I21; J13; 330; Initial Conditions; Home Resources; Intelligence; Persistence; Social Competencies; School Achievement; Kinder; Kognition; Bildungsabschluss; Deutschland